Rational identification of a novel soy-derived anxiolytic-like undecapeptide acting via gut-brain axis after oral administration. (May 2017) - Ota, Ami; Yamamoto, Akane; Kimura, Saeko; Mori, Yukiha; Mizushige, Takafumi; Nagashima, Yoshiki; Sato, Masaru; Suzuki, Hideyuki; Odagiri, Saori; Yamada, Daisuke; Sekiguchi, Masayuki; Wada, Keiji; et al.
Abstract: Here we found that the chymotryptic digest of soy β-conglycinin, a major storage protein, exhibited anxiolytic-like effects in mice. We then searched for anxiolytic-like peptides in the digest. Based on a comprehensive peptide analysis of the chymotryptic digest by high performance liquid chromatograph connected to an LTQ Orbitrap mass spectrometer and the structure-activity relationship of known peptides, we explored anxiolytic-like peptides present in the digest. FLSSTEAQQSY, which corresponds to 323–333 of the β-conglycinin α subunit [βCGα(323–333)] emerged as a candidate. Oral administration of synthetic βCGα(323–333) exhibited anxiolytic-like effects in the elevated plus-maze and open-field test in male mice. Orally administered βCGα(323–333) exhibited anxiolytic-like effects in sham-operated control mice but not in vagotomized mice. In addition, oral administration of βCGα(323–333) increased the expression of c-Fos, a marker of neuronal activity, in the nucleus of the solitary tract, which receives inputs from the vagus nerve. These results suggest that the anxiolytic-like effects were mediated by the vagus nerve. The anxiolytic-like effects of βCGα(323–333) were also blocked by antagonists of the serotonin 5-HT1A, dopamine D1 and GABAA receptors. However βCGα(323–333) had no affinity for these receptors, suggesting it stimulates the release of endogenous neurotransmitters to activate the receptors. Taken together, a soy-derived undecapeptide, βCGα(323–333), may exhibit anxiolytic-like effects after oral administration via the vagus nerve and 5-HT1A, D1 and GABAA systems. Highlights: The chymotryptic digest of soy β-conglycinin exhibited anxiolytic-like effect in mice. We found a novel anxiolytic soy undecapeptide based on a global analysis of the digest. The soy undecapeptide exhibited potent anxiolytic-like effect after oral administration. The anxiolytic-like effect was blocked by the 5-HT1A, D1 and GABAA antagonists. This is the first soy anxiolytic-like peptide coupled to the gut-brain communication.